Enemy or ally: a genomic approach to elucidate the lifestyle of Phyllosticta citrichinaensis - Valerie A Buijs; Johannes Z Groenewald; Sajeet Haridas; Kurt M LaButti; Anna Lipzen; Francis M Martin; Kerrie Barry; Igor V Grigoriev; Pedro W Crous; Michael F Seidl (G3: Genes, Genomes, Genetics, 2022)

(untitled)
AbstractMembers of the fungal genus PhyllostictaCitrusCitrus sinensisCitrus limonCitrus maximaPhyllostictaPhyllostictaPhyllosticta citrichinaensisPhyllostictaCitrusPhyllosticta citrichinaensisPhyllosticta citrichinaensisPhyllosticta